ANALISIS PENERAPAN SISTEM AKUNTANSI TER KOMPUTERISASI UNTUK MENINGKATKAN EFEKTIVITAS EFISIENSI PENYAJI LAPORAN KEUANGAN DI AHASS RIZKY MOTOR PRAMBON - Hana Eva Nurlita; Sri Luayyi; Prima Noermaning (Cahaya Ilmu Bangsa, 2025)
Accounting information systems include transaction processing cycles, use of information technology, and information system development. An accounting information system is a collection of system devices that function to record transaction data, process data, and present accounting information to internal and external parties. The research method used to examine the condition of natural objects, and the researcher himself as the instrument. The data collection technique used was inductive. MYOB is an accounting program designed to meet the need for providing accounting information, as well as as a financial report processing tool. The analysis technique used by researchers is qualitative descriptive analysis which aims to provide a true picture of the situation by collecting, analyzing and processing company data.